Connectivity and Adaptability: Evaluation of Signal Flow Scenarios in Shared Outdoor Electronic Practices on Mobile Devices - Aavanranta, Otso; Nenko, Oleksandra; Montes de Oca; Alejandro; Schlienger, Dominik (France, 2026)
Mobile devices and portable loudspeaker systems allow for a shift of electroacoustic sound practices to the outdoors. This paper reports findings from the ExoSound research project, which explores electronic co-musicianship in Nordic outdoor conditions. Three signal flow experiments that have been designed to enhance inter-musician and musician-environment connectedness are tested, evaluated, and discussed. In these successive experimental Scenarios, mobile devices are configured as individual instruments, as an output matrix using a WLAN, and an input-output network integrating a live microphone feed. The results point to a shift at the core of electroacoustic practices and aesthetics, from fixed pieces and instrumental agencies towards relationality and situatedness. Connectivity and adaptability emerge as concepts for the further development of approaches for networked electronic music making in the outdoors.
Proceedings of the 17th International Symposium on Computer Music Multidisciplinary Research